The Application of Heztec (Heating Ozone Sterilization Technology) to Increase The Productivity of Goat’s Milk in Bayu Village, Banyuwangi : Penerapan Heztec (Heating Ozone Sterilization Technology) Untuk Meningkatkan Produktivitas Susu Kambing Di Desa Bayu Kabupaten Banyuwangi - Celvin Wahyu Pradana Bagus Putra; Dimas Adidya; Rio Adjie Wiguna; Rovita Mey Andini; Monica Cyllen; Ika Yuniwati (Yayasan Ahmar Cendekia Indonesia, 2022)
The livestock sub-sector is included in one of the new sources of growth, especially for the agricultural sector and for the national economy in general. The demand for livestock commodities as a source of animal protein has increased due to an increase in population. A field survey in one of the livestock businesses in Banyuwangi is the Etawa Rofi'I dairy goat farm from Bayu Sari Village, Songgon District, Banyuwangi Regency. Rofi'I livestock has 19 goats, one goat can produce up to 2.5 liters of milk per day. With a price per liter of Rp 15,000 (fifteen thousand Rupiah). Rafi'I farmers' lack of awareness and minimal knowledge of technology for milk processing resulted in less than optimal milk productivity. Therefore, it is necessary to apply Heztect (Heating Ozone Sterilization Technology) a milk sterilization machine/pasteurization machine equipped with ozone technology, ozone technology is a technology that can produce ozone using oxygen. This technology is known to kill microorganisms such as bacteria and viruses and can also reduce the smell of goat milk. This service activity surveyed and observed more deeply the condition of partners, to understand partner problems. Then proceed with the stages of literature study, planning, and conceptualizing activities; then followed by evaluation and refinement of the machine, and ends with socialization and mentoring. The results of the application of Heztec milk produced through Heztec had a reduction in the smell of goat milk odor from 20 respondents as well as longer milk durability and a decrease in bacteria in milk. Abstrak Sub sektor peternakan termasuk dalam salah satu sumber pertumbuhan baru bagi perekonomian. Permintaan terhadap komoditi peternakan sebagai sumber protein hewani mengalami peningkatan akibat peningkatan jumlah penduduk. Salah satu usaha perternakan yang ada di Banyuwangi adalah peternakan kambing perah Etawa Rofi’I berasal dari Desa Bayu Sari Kecamatan Songgon. Perternakan Rofi’I memiliki 19 Ekor kambing, satu ekor kambing mampu menghasilkan hingga 2,5 liter susu perhari. Harga jual per liternya Rp 15.000 (lima belas Ribu Rupiah). Kurangnya kesadaran dan minimalnya pengetahuan peternak Rafi’I terhadap teknologi untuk pengolahan susu mengakibatkan produktivitas susu kurang maksimal. Oleh sebab itu perlu penerapan Heztect (Heating Ozone Sterilization Technology) merupakan mesin sterilisasi/ pasterisasi susu yang di lengkapi dengan teknologi ozon, Teknologi ozon adalah teknologi yang bisa memproduksi ozon dengan menggunakan oksigen. Teknologi dapat membunuh mikroorganisme seperti bakteri dan virus dan juga dapat mengurangi bau prengus susu kambing. Kegiatan pengabdian ini yaitu survei dan observasi lebih mendalam terhadap kondisi mitra untuk memahami permasalahan mitra. Kemudian dilanjutkan dengan tahapan studi literatur, perencanaan dan pembuatan konsep kegiatan; kemudian dilanjut evaluasi serta penyempurnaan mesin; serta diakhiri dengan sosialisasi dan pendampingan. Hasil dari penerapan Heztec susu yang diproduksi melalui Heztec memiliki pengurangan bau prengus dari 20 responden serta daya tahan susu lebih lama serta terjadinya penurunan bakteri pada susu.